SINTESIS NANOPARTIKEL CORE SHELL Fe3O4/SiO2/TiO2 SEBAGAI FOTOKATALIS PADA DEGRADASI BRILLIANT BLUE - , Armydha Dwi Susanti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Fe3O4/SiO2/TiO2 core shell nanoparticle with enhanced photocatalytic activity and adsorption capability has been synthesized. The synthesis was done by three steps i.e. sono-coprecipitation, modification using Stober method by replacing alcoxy group to control of silica shell to keep the magnetite core and sol-gel methods. Photocatalytic reaction was studied for degradation and adsorption of brilliant blue. The structured magnetite core shell readily to separate by magnetic field and increased thermal as well as chemical stability. The XRD pattern showed that the product is Fe3O4 crystal coated with SiO2 and anatase TiO2 represented as Fe3O4/SiO2/TiO2. Characterization by FTIR and TEM image showed that core shell structure Fe3O4/SiO2/TiO2 has been produced. EDX spectra showed that material consists of Fe, Si, Ti, C and O elements. DRUV spectra give Eg value of 3.37 eV. Kinetics of photocatalysis and adsorption was analyzed and it best follows pseudo second order with rate constant of degradation and adsorption are 2.7x10-3 g mg-1 min-1 and 6.69x10-2 g mg-1 min-1, respectively. The best interpretation for the experimental data was given by Langmuir isotherm model with adsorption capacity of 90.91 mg/g. This nanoparticle can be reused by magnetic field separation.